Elevated concentrations of macrophage migration inhibitory factor in serum and cerebral microdialysate are associated with delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage - Neumaier, Felix; Stoppe, Christian; Stoykova, Anzhela; Weiss, Miriam; Veldeman, Michael; Höllig, Anke; Hamou, Hussam Aldin; Temel, Yasin; Conzen, Catharina; Schmidt, Tobias Philip; Dogan, Rabia; Wiesmann, Martin; et al. (Frontiers in Neurology, 2023)
Objective Inflammation is increasingly recognized to be involved in the pathophysiology of aneurysmal subarachnoid hemorrhage (aSAH) and may increase the susceptibility to delayed cerebral ischemia (DCI). Macrophage migration inhibitory factor (MIF) has been shown to be elevated in serum and cerebrospinal fluid (CSF) after aSAH. Here, we determined MIF levels in serum, CSF and cerebral microdialysate (MD) at different time-points after aSAH and evaluated their clinical implications. Methods MIF levels were measured in serum, CSF and MD obtained from 30 aSAH patients during early (EPd1−4), critical (CPd5−15) and late (LPd16−21) phase after hemorrhage. For subgroup analyses, patients were stratified based on demographic and clinical data. Results MIF levels in serum increased during CPd5−15 and decreased again during LPd16−21, while CSF levels showed little changes over time. MD levels peaked during EPd1−4, decreased during CPd5−15 and increased again during LPd16−21. Subgroup analyses revealed significantly higher serum levels in patients with aneurysms located in the anterior vs. posterior circulation during CPd5−15 (17.3 [15.1–21.1] vs. 10.0 [8.4–11.5] ng/ml, p = 0.009) and in patients with DCI vs. no DCI during CPd5−15 (17.9 [15.1–22.7] vs. 11.9 [8.9–15.9] ng/ml, p = 0.026) and LPd16−21 (17.4 [11.7–27.9] vs. 11.3 [9.2–12.2] ng/ml, p = 0.021). In addition, MIF levels in MD during CPd5−15 were significantly higher in patients with DCI vs. no DCI (3.6 [1.8–10.7] vs. 0.2 [0.1–0.7] ng/ml, p = 0.026), while CSF levels during the whole observation period were similar in all subgroups. Conclusion Our findings in a small cohort of aSAH patients provide preliminary data on systemic, global cerebral and local cerebral MIF levels after aSAH and their clinical implications. Clinical trial registration ClinicalTrials.gov, identifier: NCT02142166.